Co-existence of hepatitis A and adult Reye's syndrome. Issue 1 (July 1997) - Duerksen, D R; Jewell, L D; Mason, A L; Bain, V G
Abstract : Reye's syndrome is most frequently seen in children but has also been described in adults. This syndrome is usually associated with ingestion of 5-aminosalicylates (ASA) or infection with influenza A, influenza B, or varicella virus. A case of Reye's syndrome in a 47 year old, previously healthy woman precipitated by ingestion of ASA and acute hepatitis A virus infection is described. Reye's syndrome was diagnosed on the basis of her clinical course, and the presence of hepatic microvesicular steatosis and characteristic electron microscopic changes in the hepatocyte mitochondria. The diagnosis of hepatitis A was based on higher amino-transferase values than would be expected in Reye's syndrome alone, viral serology including the presence of hepatitis A IgM and the demonstration of hepatitis A virus RNA on liver biopsy by in situ hybridisation. Mitochondrial injury has been demonstrated in acute hepatitis A which, in addition to ASA, may have precipitated Reye's syndrome in this patient. The association between hepatitis A and Reye's syndrome has not been reported before. As hepatitis A virus infection is not sought routinely in patients with Reye's syndrome, the frequency of this association is unknown.